2013
DOI: 10.1371/journal.pone.0083591
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia as a Cause of Fever in Ambulatory, HIV-Infected Mozambican Adults: Results and Policy Implications from a Prospective Observational Study

Abstract: Fever is typically treated empirically in rural Mozambique. We examined the distribution and antimicrobial susceptibility patterns of bacterial pathogens isolated from blood-culture specimens, and clinical characteristics of ambulatory HIV-infected febrile patients with and without bacteremia. This analysis was nested within a larger prospective observational study to evaluate the performance of new Mozambican guidelines for fever and anemia in HIV-infected adults (clinical trial registration NCT01681914, www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…42,43 Study coordinators recorded subjects' demographic and medical information. Study clinicians reviewed medical histories (including TB screening questions) and laboratory data, conducted physical examinations, and determined the most likely cause(s) of each subject's anemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Study coordinators recorded subjects' demographic and medical information. Study clinicians reviewed medical histories (including TB screening questions) and laboratory data, conducted physical examinations, and determined the most likely cause(s) of each subject's anemia.…”
Section: Methodsmentioning
confidence: 99%
“…We have described our methods for pathogen identification, antibiotic susceptibility testing, and quality control of blood cultures elsewhere. 42 …”
Section: Methodsmentioning
confidence: 99%
“…9 Briefly, ambulatory HIV-infected adults ≥18 years old with axillary temperature ≥37.5° C or history of fever (preceding 24 h) were eligible. Patients were ineligible if rapid preliminary evaluation detected guideline-determined danger signs or if unable to communicate in Portuguese or Echuabo (a local language).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that the trimethoprim-sulfamethoxazole impact on the oral microflora36 37 may affect the community profile. This could occur with leukaemic children as they use antibiotics continuously, which differs in the case of healthy children.…”
Section: Discussionmentioning
confidence: 99%